Pengaruh Leverage dan Profitabilitas Terhadap Tax Avoidance Dengan Kepemilikan Institusional Sebagai Variabel Moderasi: Studi Empiris Pada Perusahaan Manufaktur Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Nelly Rahmawati; Sri Ayem (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to examine whether the effect of leverage and profitability on tax avoidance with institutional ownership as a moderating variable. Data were analyzed using SPSS 27. Method: This study utilizes quantitative data from the official websites of food and beverage sector companies, specifically manufacturing firms listed on the Indonesia Stock Exchange (IDX) in the 2021-2024 period with purposive sampling technique resulting 177 in total annual financial reports analyzed. The analytical methods used include multiple linier regression and subgroup analysis. Finding: The results of this study indicate that leverage has a possitive influence toward tax avoidance, profitability has a possitive effect in tax avoidance, institutional ownership can moderate the possitive of leverage on tax avoidance, and institutional ownership cannot moderate the possitive effect of profitability on tax avoidance. Novelty: This research is novel because the researches added a new time period 2021-2024. This research can make a significant contribution to the literature on tax avoidance and corporate finance, and can help improve understanding of how institutional ownership affects the relationship between leverage and profitability on tax avoidance.